2002
DOI: 10.1046/j.1365-2958.2002.02795.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of thioredoxins in the response of Saccharomyces cerevisiae to oxidative stress induced by hydroperoxides

Abstract: SummaryGlutaredoxins and thioredoxins are highly conserved, small, heat-stable oxidoreductases. The yeast Saccharomyces cerevisiae contains two gene pairs encoding cytoplasmic glutaredoxins (GRX1, GRX2) and thioredoxins (TRX1, TRX2), and we have used multiple mutants to determine their roles in mediating resistance to oxidative stress caused by hydroperoxides. Our data indicate that TRX2 plays the predominant role, as mutants lacking TRX2 are hypersensitive, and mutants containing TRX2 are resistant to these o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
140
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(152 citation statements)
references
References 48 publications
11
140
0
1
Order By: Relevance
“…We found that both grx1Δ and trx2Δ showed sensitivity to oxidative stress (Fig. 7M), which has also already been reported reported (Collinson et al, 2002;Garrido and Grant, 2002;Luikenhuis et al, 1998) while on α-factor exposure, grx1Δ and trx2Δ strains showed significantly higher growth as compared to WT strain (Fig. 7O) (controls are shown in Fig.…”
Section: Glutathionylation and Deglutathionylation Enzymes Regulate Csupporting
confidence: 87%
“…We found that both grx1Δ and trx2Δ showed sensitivity to oxidative stress (Fig. 7M), which has also already been reported reported (Collinson et al, 2002;Garrido and Grant, 2002;Luikenhuis et al, 1998) while on α-factor exposure, grx1Δ and trx2Δ strains showed significantly higher growth as compared to WT strain (Fig. 7O) (controls are shown in Fig.…”
Section: Glutathionylation and Deglutathionylation Enzymes Regulate Csupporting
confidence: 87%
“…For example, the gene TRX2 is a highly conserved oxydoreductase, required to maintain the redox homeostasis of the cell. In S. cerevisiae, thioredoxin TRX2 and thioredoxin reductase TRR1 were shown to be necessary to protect the cell against oxidative stress induced by the presence of ROS compounds in condition H 2 O 2 (Boisnard et al, 2009) or exposure to dithiothreitol (DTT) (Garrido and Grant, 2002). This agrees with the review of Rodrigues-Pousada et al (2010), in which Yap2p and Yap4p were described as involved in several types of stress responses, including oxidative stress (Cohen et al, 2002;Nevitt et al, 2004).…”
Section: Potential Roles In Oxidative Stress Response For Others Membsupporting
confidence: 85%
“…26 In addition, a functional link between Grx and Trx expressions has also been described in yeast, where a lack of Trx causes a decrease in GSH levels, which are compensated for by an increased Grx expression. 27 A reduction of GSH levels has been previously demonstrated in AD brain, 28 suggesting the possibility of a similar mechanism.…”
Section: Discussionmentioning
confidence: 67%
“…Ab (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and Ab were purchased from Sigma-Aldrich (Stockholm, Sweden). Ab(1-42) was from US Peptide (Rancho Cucamonga, CA, USA) and dissolved in serum-free minimum essential medium (MEM).…”
Section: Methodsmentioning
confidence: 99%